2004
DOI: 10.1016/j.ymthe.2004.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Prostate Cancer with Conditionally Replicative Adenovirus Using PSMA Enhancer

Abstract: Prostate cancer is the second most commonly diagnosed cancer in men and accounts for significant mortality and morbidity in the United States. Initially androgen-dependent, prostate cancer ultimately becomes androgen-independent, which makes the disease extremely difficult to cure. In this study, we examined the use of conditionally replication-competent adenovirus for the treatment of hormone-independent prostate cancer. We utilized PSME, an enhancer element for prostate-specific PSMA expression, to control v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…26 Other CRADs with prostate-specific promoters have been reported. 18,[27][28][29] The CV706 adenovirus, where the E1A gene is under the control of the PSE sequence (the minimal PSA promoter with the upstream PSA enhancer), was used in a phase I clinical trial with a demonstrated good safety profile and therapeutic effects. 19 The PSA promoter is, however, dependent on a functional androgen receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Other CRADs with prostate-specific promoters have been reported. 18,[27][28][29] The CV706 adenovirus, where the E1A gene is under the control of the PSE sequence (the minimal PSA promoter with the upstream PSA enhancer), was used in a phase I clinical trial with a demonstrated good safety profile and therapeutic effects. 19 The PSA promoter is, however, dependent on a functional androgen receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a CRAD against prostate cancer has been reported where the E1A gene is under the control of the PSMA enhancer. 29 The PSMA enhancer-controlled CRAD showed good efficacy at low levels of testosterone and it could theoretically be used for prostate cancer patients treated with androgen withdrawal. However, the transcriptional activity of the PSMA enhancer is downregulated at physiological levels of testosterone, which limits the use of the PSMA enhancer-controlled CRAD in patients that are not subject to androgen withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the utility of DIMN as a new generation of AR antagonists for the treatment of CRPC, the more aggressive form of prostate cancer, we next determined the inhibitory effect of DIMN on the proliferation of later stage androgenindependent C4 -2 and CWR22rv cells, which grow independently of androgens while expressing AR protein (47,65). The effect of DIMN on the proliferation rate of C4 -2 cells was measured by the MTS assay.…”
Section: Suppression Of Androgen-induced Ar Target Gene Expression Bymentioning
confidence: 99%
“…The advantage of using the replication-competent adenoviruses for therapeutic gene delivery is that it can selectively replicate and spread in malignant tumor tissues, and finally lead to remarkably increased therapeutic gene expression in tumor cells accompanying adenoviral replication and spread. The current strategy to generate tumor-selective replication-competent adenovirus is to replace the adenovirus E1 gene promoter with other tumor or tissue-specific promoter [8,9]. Since human telomerase reverse transcriptase (hTERT) is over-expressed in all types of NSCLC, but is inactivated in normal cells [10], in the present study, we chose the hTERT promoter to drive adenoviral E1A gene expression and generated a tumor-selective replication-competent adenoviral vector.…”
Section: Introductionmentioning
confidence: 99%